Dragon Fruit Ice Cream Sebagai Inovasi Tumbuh Kembang Anak Pada Madrasah Ibtidaiyah Al-Fitrah, Makassar - Arfah, Aryati; Lantara, Niniek A.; Suriyanti, Suriyanti (Jurnal BALIRESO, 2026)
This community engagement program aims to enhance economic capacity and nutritional awareness through the development of value-added food products using local commodities. Implemented at Madrasah Ibtidaiyah Al-Fitrah in Makassar, the program introduced a simple technology for producing antioxidant-rich dragon fruit ice cream as a healthy snack alternative for children. Training covered production techniques, hygiene practices, basic cost recording, and simple marketing strategies. The results show improvements in participants’ technical skills, sanitation awareness, and ability to set feasible selling prices while identifying small-scale business opportunities. The program contributes to strengthening household economic potential and promoting community empowerment through locally based food innovation.